THU0148 Economic Considerations and Patients' Preferences Affect Treatment Selection for Rheumatoid Arthritis Patients: A Discrete Choice Experiment among European Rheumatologists. (15th July 2016) - Hifinger, M.; Hiligsmann, M.; Ramiro, S.; Watson, V.; Severens, H.; Fautrel, B.; Uhlig, T.; van Vollenhoven, R.; Jacques, P.; Detert, J.; Canas da Silva, J.; Scirè, C.; et al.
Abstract : Background: Economic considerations and patient preferences are increasingly important when choosing treatments. It is not known to what extent rheumatologists across Europe account for these factors when changing drug therapies in patients with active rheumatoid arthritis (RA). Objectives: To compare the value that rheumatologists across Europe attach to patients' preferences and economic aspects when choosing treatments for rheumatoid arthritis (RA) patients. Methods: In a discrete choice experiment European rheumatologists chose between two hypothetical drug treatments for a patient with moderate disease activity. Treatments differed in five attributes: efficacy (improvement and achieved state on disease activity), safety (probability of serious adverse events), patient's preference (level of agreement), medication costs and cost-effectiveness (incremental cost-effectiveness ratio (ICER)). A Bayesian efficient design defined the fourteen choice sets and a random parameter logit model was used to estimate relative treatment preferences for rheumatologists across countries. β Coefficients presented in table 1 indicate whether the attribute has a negative or positive effect on the rheumatologists' preference Cluster analyses and latent class models were applied to understand preference patterns across countries and among individual rheumatologists. Results: Responses of 559 rheumatologists from 12 European countries were included in the analysis (49% females, mean age 48 years). In all countries, efficacy dominated the treatment decision followed by economic considerations and patient's preferences. Across countries, patient's agreement with the treatment was associated with an increased treatment preference of rheumatologists and a stronger, negative impact on rheumatologists treatment preference was seen when patents dislike treatments. The economic aspect also played an important role. Higher economic burden was consistently associated with decreased treatment preference. Interestingly, medication costs contributed significantly in all countries, whereas cost-effectiveness was only significant in 9 of 12 countries (table).Latent class models revealed four respondent profiles: one of which traded off all attributes, and the remaining three classes that disregarded ICER. Among individual rheumatologists, 57% disregard ICER in treatment choices, and these were more likely to be located in Italy, Romania, Portugal or France (cluster 2, table) Conclusions: Overall, European rheumatologists are willing to trade between treatment efficacy, patients' treatment preferences and economic considerations. However, the degree of trade-off differs between countries and among individuals. Disclosure of Interest: None declared